Formulation of Distinction-Based MBKM Design Sharia Economics Study Program (Mapping Study of Potential Partner Institutions of UIN Prof. K.H. Saifuddin Zuhri Purwokerto) - Dewi Laela Hilyatin; Tri Mulatsih Pudjileksani; Gebyar Cahya Aditya; John Paul Banac; Sugeng Riyadi (el-Jizya: Jurnal Ekonomi Islam, 2025)
This research, titled "Formulation of MBKM Design Based on the Distinction of the Islamic Economics Study Program: A Study on Mapping Potential Partner Institutions of UIN Prof. K.H. Saifuddin Zuhri Purwokerto," aims to explore and develop a specific design of the Merdeka Belajar Kampus Merdeka (MBKM) curriculum that aligns with the unique characteristics of the Islamic Economics Study Program (Prodi Ekonomi Syariah) at UIN SAIZU. The MBKM curriculum is an initiative introduced by the Indonesian Ministry of Education to provide students with more flexible learning opportunities, including collaboration with external institutions. This study seeks to map potential partner institutions that can collaborate with UIN SAIZU in implementing the MBKM curriculum. The research employs a qualitative approach, involving document analysis, interviews, and surveys to identify and evaluate the institutions that align with the program's vision and mission. Key criteria for partnership include adherence to sharia principles, contributions to the field of Islamic economics, and the capacity to provide students with practical experiences in line with MBKM objectives. The results of this research present a structured MBKM design tailored to the distinction of the Islamic Economics Study Program, including a list of recommended partner institutions. This design aims to enhance students' competencies by bridging academic knowledge and practical experiences while maintaining the integrity of Islamic economic principles. The findings of this research are expected to contribute to the successful implementation of the MBKM curriculum at UIN SAIZU and serve as a model for other universities seeking to develop their MBKM programs based on their distinct academic disciplines.